Investigating Attentional Demands of a Continuous Motor Task Using Probe Reaction Time and Measures of Corticospinal Excitability - Sadler, Christin (Université d'Ottawa / University of Ottawa, 2020)
The performance of a second motor task during an ongoing motor task requires attention. Currently, it is unclear how the attentional demands of a primary continuous motor task affect the preparation and execution of a second motor task. The purpose of the present experiment was to investigate whether the attentional demands of a cyclical primary motor task vary with location within a movement cycle, and whether these variations impact response preparation of a second motor task reflected as differences in premotor reaction time (RT) and/or measures of corticospinal excitability. Participants (N=20) performed a continuous tracking task that involved cycles of wrist flexion and extension with their left hand. A probe RT task involving isometric wrist extension was performed with the right hand in response to auditory stimuli (80 dB and 120 dB) that were triggered as the left hand cycled through one of five locations. On separate trials, transcranial magnetic stimulation (TMS) was applied over the left primary motor cortex to assess corticospinal excitability associated with the probe RT task. The results revealed that probe RT latencies were significantly longer and motor evoked potential (MEP) amplitudes were significant larger when the RT task was probed when the left hand was in the middle of a movement cycle. Together, these results suggest that there are moments within a continuous motor task that have larger attentional demands, and these variations have an impact on advance response preparation of a second motor task as measured by differences in premotor RT and measures of corticospinal excitability.
Keywords: Response preparation; Probe Reaction Time; Startling Acoustic Stimulus; Transcranial Magnetic Stimulation